Effect of reinforced, targeted in-person education using the Jessa Atrial fibrillation Knowledge Questionnaire in patients with atrial fibrillation: A randomized controlled trial. (March 2019) - Desteghe, Lien; Engelhard, Lara; Vijgen, Johan; Koopman, Pieter; Dilling-Boer, Dagmara; Schurmans, Joris; Delesie, Michiel; Dendale, Paul; Heidbuchel, Hein
Background: The knowledge level of atrial fibrillation patients about their arrhythmia, its consequences and treatment is poor. The best strategy to provide education is unknown. Aim: To investigate the effect of reinforced targeted in-person education using the Jessa Atrial fibrillation Knowledge Questionnaire (JAKQ). Methods: Sixty-seven atrial fibrillation patients were randomized to standard care (including brochures) or targeted education. Follow-up visits were scheduled after one, three, six and 12 months. Targeted education during each visit focused on the knowledge gaps revealed by the JAKQ. Patients completed two questionnaires to assess their quality of life and symptom profile. Adherence to non-vitamin K antagonist oral anticoagulants was measured using electronic monitoring. Results: Sixty-two patients (31 education; 31 standard care) completed follow-up. Median baseline score on the JAKQ was similar in education (62.5%) and standard care group (56.3%; p =0.815). The intervention group scored significantly better over time (one month: 75.0%, 12 months: 87.5%; p <0.001) whereas there was no significant improvement in the control group (one month: 62.5%, 12 months: 62.5%; p =0.085). Providing targeted education after completion of the JAKQ required on average 6.9±4.6 min. Some improvements in quality of life, symptom burden and adherence were shown, without significant differences between the two groups ( p -values between 0.282 and 0.677). Conclusion: The JAKQ is an effective tool for providing individualized education. A first targeted educational session significantly improved patients' knowledge level. Additional educational sessions maintained and strengthened this effect. A larger scale study is warranted to evaluate the impact on adherence and outcome measures.